(untitled) (World Bulletin of Social Sciences, 2025)
The article highlights the state of transport communication in Karakalpakstan during the Second World War. With the beginning of the war, the entire transport system of the republic was reorganized. All its activities were aimed at meeting the needs of the front. Most of the cars and tractors were mobilized to the front, shipping and railways were heavily burdened. The republic had sea and river transport, through which all cargo flows were carried out. The republic had transport links through the Aral and Amu Darya shipping lines and had access to large railway lines.